Antimicrobial properties of Kalanchoe blossfeldiana: a focus on drug resistance with particular reference to quorum sensing-mediated bacterial biofilm formation. (1st April 2015) - Sarkar, Ratul; Mondal, Chaitali; Bera, Rammohan; Chakraborty, Sumon; Barik, Rajib; Roy, Paramita; Kumar, Alekh; Yadav, Kirendra K; Choudhury, Jayanta; Chaudhary, Sushil K; Samanta, Samir K; Karmakar, Sanmoy; et al.
Abstract: Objectives: This study attempts to investigate the antimicrobial properties of K alanchoe blossfeldiana with a particular reference to quorum sensing (QS)-mediated biofilm formation. Methods: The methanol extract of K . blossfeldiana leaves (MEKB) was evaluated for antimicrobial properties including QS-controlled production of biofilm (including virulence factor, motility and lactone formation) in P seudomonas aeruginosa . Methanol extract of K . blossfeldiana was also evaluated for anti-cytokine (tumour necrosis factor-alpha, interleukin-6 and interleukin-1 beta) properties in peripheral blood mononuclear cells (PBMC). Key findings: Methanol extract of K . blossfeldiana exhibited antimicrobial effect on clinical isolates, as well as standard reference strains. P seudomonas aeruginosa exposed to MEKB (subminimum inhibitory concentration (MIC)) displayed reduced biofilm formation, whereas supra-MIC produced destruction of preformed biofilms. Methanol extract of K . blossfeldiana reduced the secretion of virulence factors (protease and pyoverdin) along with generation of acyl homoserine lactone (AHL). Confocal laser scanning microscopy images indicate reduction of biofilm thickness. The extract also reduced cytokine formation in lipopolysaccharide-stimulated PBMC. Conclusions: K alanchoe blossfeldiana was found to interfere with AHL production, which in turn may be responsible for downregulating QS-mediated production of biofilm and virulence. This first report on the antibiofilm and anticytokine properties of this plant may open up new vistas for future exploration of this plant for combating biofilm-related resistant infections.